Simultaneous Determination of Six Acidic Pesticides, Including 2,4-DB and 2,4,5-T with No Established MRL in Korea Using LC-MS/MS and QuEChERS for the Safety of Imported Agricultural Products - Joon-Kyung Oh; Jae-Hyeong Kim; Ga-Eul-Hae An; Hee-Ra Chang (Foods)
The use of pesticides is essential for the production of high-quality agricultural products. However, the repeated application of pesticides has led to the contamination of environments, such as the atmosphere, soil, and surface water, affecting ecosystems and leading to residues on crops, which pose potential risks to human health. Accordingly, regulations regarding pesticide usage, application frequency, timing, and maximum residue limits have been established to manage residual pesticides. The Positive List System (PLS), with a default tolerance of 0.01 ppm, has been applied to both domestic and imported agricultural products for which no established maximum residue limits (MRLs) exist in Korea. This study developed a multi-residue analytical method for the simultaneous determination of six pesticides, including 2,4-DB and 2,4,5-T, for which no domestic MRLs have been established, as well as for 2,4-D, 4-CPA, Dicamba, and Dichlorprop, for the management of imported agricultural products. The target pesticides were extracted and purified using the QuEChERS method and quantified by LC-MS/MS. The analytical method was validated according to the CODEX (CAC/GL 40-1993) and the Guidelines of Standard Procedures of Test Methods for Foods and Other Substances established by the MFDS. Using the developed and validated analytical method, monitoring of imported agricultural products was conducted.